‘Preach the World’: Canadian Imperialism and Missionary Outreach at the Montreal Diocesan Theological College, 1892-1903 - Mills, Sean (Journal of the Canadian Church Historical Society, 2001)
Keywords: Anglicans; Missions; Protestants; Théologie

The Empire Within: Postcolonial Thought and Political Activism in Sixties Montreal - Mills, Sean (McGill-Queen's University Press, 2010)
Keywords: Groupes populaires; Idéologies

Québécoises Deboutte!: Le Front de libération des femmes du Québec, le Centre des femmes et le nationalisme - Mills, Sean (Mens, 2004)
Keywords: Femmes; Féminisme; Nationalisme

August 1, 1930: Canadians Thrill to the Arrival of the First Dirigible - Mills, Sean (The Beaver, 2003)

When Democratic Socialists Discovered Democracy: The League for Social Reconstruction Confronts the Quebec Problem - Mills, Sean (Canadian Historical Review, 2005)
Keywords: Forsey, Eugene Alfred; Gordon, John King; Idéologies; Lewis, David; Marsh, Leonard; Nationalisme; Scott, Frank R.; Socialistes

Quebec, Haiti, and the Deportation Crisis of 1974 - Mills, Sean (Canadian Historical Review, 2013)
Keywords: Haïtiens

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

A place in the Sun: Haiti, Haitians, and the Remaking of Quebec - Mills, Sean (Study on the History of Quebec/Études d'histoire du Québec, 2016)
Keywords: Haïtiens

Democracy in Music: Louis Metcalf's International Band and Montreal Jazz History - Mills, Sean (Canadian Historical Review, 2019)
Keywords: Idéologies; Musicien; Musique

La démocratie dans la musique : l’International Band de Louis Metcalf et l’histoire du jazz à Montréal - Mills, Sean (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Idéologies; Musicien; Musique

The Empire Within: Montreal, the Sixties, and the Forging of a Radical Imagination - Mills, Sean William (Université Queen's, 2008)
Keywords: Groupes populaires; Idéologies

Democracy, Dissent, and the City: Cross-Cultural Encounters in Sixties Montreal - Mills, Sean (The Sixties in Canada: a Turbulent and Creative Decade, 2009)
Keywords: Femmes; Féminisme; Noirs; Travail

Contester l’empire. Pensée postcoloniale et militantisme politique à Montréal, 1963-1972 - Mills, Sean (Hurtubise, 2011)
Keywords: Groupes populaires; Idéologies

La langue de la libération / The Language of Liberation - Mills, Sean (Des actions parlantes. Aspects de la culture québécoise des années 1960 et 1970 / Actions that speaks. Aspects of Quebec Culture in the 1960s and 1970s, 2012)
Keywords: Anglophones; Francophones; Université McGill

La gauche montréalaise, le nationalisme et les années soixante - Mills, Sean (Contester dans un pays prospère: l'extrême gauche en Belgique et au Canada, 2007)
Keywords: Groupes populaires; Idéologies; Nationalisme

Statesman of the Piano: Jazz, Race, and History in the life of Lou Hooper - Mills, Sean; Fillion, Eric; Rochat, Désirée (McGill-Queen's University Press, 2023)
Keywords: Musique

Québécoises deboutte! Nationalism and Feminism in Quebec, 1969-75 - Mills, Sean (Contemporary Quebec: Selected Readings and Commentaries, 2011)
Keywords: Femmes; Féminisme; Nationalisme